A molecular investigation of Huntington disease; origins of the mutation and current prevalence in South Africa - Baine, Fiona Eugenie Kebirungi (Division of Human Genetics, 2016)
Huntington disease (HD) is a devastating neurodegenerative condition characterised by a triad of symptoms: behavioural/psychiatric changes, cognitive decline and movement disorder. The dominantly inherited disease-causing mutation is an expanded trinucleotide (CAG) repeat in the Huntingtin(HTT) gene. Clinical symptoms are believed to be the result of degeneration of specific neuronal populations that are susceptible to the presence of a toxic expanded protein product. The disease is incurable and following the onset of symptoms, is progressively debilitating over 10-20 years and eventually fatal. Although typical epidemiological studies of prevalence are challenging for a genetic disorder such as HD, family studies and various other methods of ascertainment have been used to estimate its occurrence in different populations. Prevalence is therefore known to vary geographically; population-specific haplotypes have been hypothesised to be the basis of this variation between ethnic groups. High prevalence estimates for populations with European ancestry led to the supposition that the HD mutation was introduced to different regions by Europeans. In South Africa, a survey in the 1970s estimated that the prevalence of HD in the white and coloured subpopulations was similar at 2 per 100 000 individuals; while that in the black subpopulation was significantly lower, at less than 0.01 per 100 000 individuals. Molecular genetic analyses have since revealed links between the white and coloured subpopulations which would explain the similarity in prevalence; however, our knowledge of the genetics of HD in the black subpopulation, has been sorely lacking. This study provides, for the first time, a comprehensive analysis of the HTT gene in an African population. An evaluation of the normal distribution of CAG-tract sizes highlighted significant differences between the subpopulations. Haplotype analysis identified population-specific disease-associated haplotypes, confirming distinct origins of the HD mutation in the different subpopulations. In a coloured family with the rare juvenile form of the disease, DNA sequencing revealed no novel variants within the immediate vicinity of the CAG-tract that could be associated with the observed instability. This indicates that genome-wide analyses may be more useful in identifying factors related to repeat instability and future investigations are planned for a cohort of South African patients affected by juvenile onset HD.